Educación: La influencia de los sistemas de creencias - Fernández Montt , René; Clara, Luis Juan B. (Nómadas. Critical Journal of Social and Juridical Science, 2010)
In this article we are a historical review of the influence of belief systems in education from antiquity to modern times in Chile. Our aim is far from judging the work of the various systems of beliefs and their influence on education, but we seek to establish the importance of it and analyze it according to the most important religious conglomerates in Chile. Belief systems have developed a leading role in the historical evolution that has taken education in the world and particularly in Chile. In most cases the influence of major religious cluster has helped increase the supply of education, enhancing public efforts to deliver quality education and to transmit values and universally accepted principles. For this reason, this essay will describe the historical influences that have had major belief systems such as the Catholic Church, the Evangelical Church, and Freemasonry.
Keywords: Beliefs; Religion; Freemasonry; Education; Catholic Church; Evangelical Church